High-precision molecular measurements in an electrostatic fluidic trap - Bespalova, M (2022)
Measurement of molecular properties at the single-molecule level can reveal valuable information, often hidden in ensemble measurements. In this Thesis, we present a range of novel high-precision molecular measurements in solution enabled by the electrostatic fluidic trapping approach.